Территория Пруто-Днестровского междуречья в период формирования Киевской Руси и Галицко-Волынского княжества - Возний, Ігор (Комрат : КГУ, 2020)
The article considers the process of entering the territory of the Siret and Dniester rivers to the Kiev state, displaying political and historical events that had a significant impact on the local population during the struggle against the accession process and the Christianization of Kiev. The formation of the Galicia-Volyn principality, and the value in this.
Keywords: Kievan Rus; the Principality of Galicia-Volhynia; Tivertsy; Croats; city; reign